2000
DOI: 10.1021/jp992208g
|View full text |Cite
|
Sign up to set email alerts
|

Interaction between Aromatic Residues. Molecular Dynamics and ab Initio Exploration of the Potential Energy Surface of the Tryptophan−Histidine Pair

Abstract: Empirical force fields for minimum searching in the tryptophan-histidine intermolecular energy surface were used. Fourteen principal minima were identified. For each of these structures the intermolecular energies were computed by using single point correlated ab initio calculation with a split valence and a correlation consistent valence double-ζ basis set. The force field determined complexes have much larger correlated ab initio stabilization energy than those reported in previous studies where a purely ab … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
65
0

Year Published

2000
2000
2010
2010

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(69 citation statements)
references
References 30 publications
4
65
0
Order By: Relevance
“…6 We found that there was a reasonable correlation between the two landscapes, and that molecular mechanics landscapes in turn were correlated to some extent with the distributions of side-chain packing geometries in protein structures. This and the other studies 5,9 suggested that molecular mechanics potentials capture p-p and cation-p interactions to an extent greater than might be expected for simple point charge-based models, but that there is still considerable room for improvement.…”
Section: Introductionmentioning
confidence: 74%
See 1 more Smart Citation
“…6 We found that there was a reasonable correlation between the two landscapes, and that molecular mechanics landscapes in turn were correlated to some extent with the distributions of side-chain packing geometries in protein structures. This and the other studies 5,9 suggested that molecular mechanics potentials capture p-p and cation-p interactions to an extent greater than might be expected for simple point charge-based models, but that there is still considerable room for improvement.…”
Section: Introductionmentioning
confidence: 74%
“…p-p, cation-p and hydrophobic interactions play important roles in stabilizing protein structures and have been investigated using quantum chemistry calculations, [3][4][5][6][7][8][9][10][11][12][13][14] molecular mechanics calculations, 5,9,15,16 and protein structural analysis. [17][18][19][20][21][22][23] Quantum chemistry and molecular mechanics calculations have identified the energy minima for pairs of interacting residues, and protein structural analysis has described the distributions of interaction geometries for different residue pairs.…”
Section: Introductionmentioning
confidence: 99%
“…Post Hartree–Fock methods as Møller Plesset perturbation theory (MP) (51) and Coupled Cluster theory (68,69) have been tested in the past for their ability to describe the interaction energy between two benzene rings, RNA/DNA base pairs and aromatic amino acids (26,27,70,71). The use of the 6-31G*(0.25) basis set at the MP2 level containing one set of diffuse polarization functions with an exponent of 0.25 on second row elements, has been shown by Hobza and Sponer (72) to be a good compromise between computational cost and quality.…”
Section: Theory and Computational Detailsmentioning
confidence: 99%
“…Also in the case of the precursor molecule (lithocholic acid ethane-1,2diol diester) the folded structure is energetically favoured. 27 In conclusion, three novel bile acid-based dimers were synthesized, possessing several active sites for molecular recognition: three pairs of carboxylic groups, one pair of aromatic -systems, and two rigid steroid skeletons. Further, the closed conformation of 2 is energetically more stable than that of the precursor, which suggests that an attractive interaction exists between aromatic rings.…”
Section: Which Ismentioning
confidence: 99%